2021
DOI: 10.4414/smw.2021.w30057
|View full text |Cite
|
Sign up to set email alerts
|

Interseasonal RSV infections in Switzerland – rapid establishment of a clinician-led national reporting system (RSV EpiCH)

Abstract: In anticipation of an interseasonal respiratory syncytial virus (RSV) epidemic, a clinician-led reporting system was rapidly established to capture RSV infections in Swiss hospitals, starting in January 2021. Here, we present details of the reporting system and first results to June 2021. An unusual epidemiology was observed with an interseasonal surge of RSV infections associated with COVID-19-related non-pharmacological interventions. These data allowed real-time adjustment of RSV prophylaxis guidelines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…However, this marked upsurge is likely to have been further precipitated by the widespread relaxation of COVID-19 mitigation measures such as travel restrictions, school closures, use of face masks and physical distancing. The findings are indeed consistent with the widespread resurgence of other community-transmitted respiratory infections, whose circulation in most of Europe had until recently largely ceased [ 11 , 12 ]. The interruption in the transmission of respiratory and enteric viruses, including EV-D68, has probably created large cohorts of susceptible young children without prior exposure or immunity to any such virus, potentially creating the conditions for largescale outbreaks of severe respiratory disease in this age group this winter.…”
Section: Discussionsupporting
confidence: 78%
“…However, this marked upsurge is likely to have been further precipitated by the widespread relaxation of COVID-19 mitigation measures such as travel restrictions, school closures, use of face masks and physical distancing. The findings are indeed consistent with the widespread resurgence of other community-transmitted respiratory infections, whose circulation in most of Europe had until recently largely ceased [ 11 , 12 ]. The interruption in the transmission of respiratory and enteric viruses, including EV-D68, has probably created large cohorts of susceptible young children without prior exposure or immunity to any such virus, potentially creating the conditions for largescale outbreaks of severe respiratory disease in this age group this winter.…”
Section: Discussionsupporting
confidence: 78%
“…Hammerstein et al reported a shift in the usual RSV season in both infants and children, which coincided with the lifting of PHSMs and a local decline in COVID-19 cases. 68 A change in RSV seasonality was also found in Germany. A dramatic decrease of RSV cases was observed in winter during 2020 to 2021.…”
Section: Dovepressmentioning
confidence: 82%
“…In January 2021, the multicenter database EpiCH began collecting data on RSV infections among hospitalized children in Switzerland [12]. Our CLRS expanded upon EpiCH's approach by additionally collecting data on the necessity for respiratory support, an aspect which enabled reporting on national and potentially regional impacts for general wards and intensive care units.…”
Section: Discussionmentioning
confidence: 99%